Beclomethasone at different doses for chronic asthma - Adams, Nick P (Cochrane Database Syst Rev, 1999)
BACKGROUND: Beclomethasone dipropionate (BDP) is available in a wide range of daily doses for the treatment of long‐term asthma. OBJECTIVES: To assess the evidence for a dose response relationship for BDP in the treatment of long‐term asthma. SEARCH METHODS: We searched the Cochrane Airways Group trial register, Cochrane Controlled Trials Register (The Cochrane Library issue 1 1999) and references lists of articles. Authors and Glaxo Wellcome UK were contacted to identify eligible studies. We also hand searched the proceeding from relevant respiratory society meetings, the British Journal of Clinical Research and the European Journal of Clinical Research for studies. SELECTION CRITERIA: Prospective, randomised trials comparing two or more daily doses of BDP in patients over the age of two years with long‐term asthma. DATA COLLECTION AND ANALYSIS: Trials were selected for inclusion and scored for quality by two reviewers. Data were extracted by one reviewer. Authors were contacted to clarify details of study design and retrieve missing data. MAIN RESULTS: 15 trials were included. Methodological quality was variable. Studies rarely gave a clear indication of the degree of asthma control at baseline. Less than two‐fold to five‐fold dose differences were assessed by different studies. The results are reported as weighted mean differences (WMD) with 95% confidence limits (95% CI). The number of trials (N) contributing to each outcome is stated. In non‐oral steroid treated asthmatics a small advantage of BDP 800 mcg/d over 400 mcg/d was apparent for improvement in morning peak expiratory flow rate (PEFR) compared to baseline, WMD 11 L/min (95% CI 4 to 19 L/min) N=2; improvement in forced expired volume in one second (FEV1) compared to baseline, WMD 9 ml (95% CI 3 to 140) N=1; and reduction in night‐time symptom score compared to baseline, WMD 0.13 (95% CI 0.04 to 0.22) N=1. Studies that assessed BDP 1000 v 500 mcg/d and BDP 1600 v 400 mcg/d demonstrated significant advantage of higher dose over lower dose for histamine bronchial hyper‐responsiveness (BHR) and percentage improvement in FEV1 compared to baseline. No differences between higher and lower daily doses of BDP were apparent for daytime symptoms, withdrawals due to asthma exacerbation, oropharyngeal side effects or measures of hypothalamo‐pituitary‐adrenal (HPA) function. No difference in prednisolone sparing effect was apparent when comparing high dose and low dose BDP in oral corticosteroid (OCS) dependent patients. AUTHORS' CONCLUSIONS: BDP appears to demonstrate a shallow dose response effect in long‐term asthma for a small number of efficacy outcomes over range of daily doses from 400 mcg/d to 1600 mcg/d, although the clinical significance of the improvements afforded by higher doses is questionable.